2020
DOI: 10.1097/yco.0000000000000605
|View full text |Cite
|
Sign up to set email alerts
|

The role of diet in preventing and reducing cognitive decline

Abstract: Purpose of Review This review summarizes the most recent evidence regarding the effects of diet in preventing and reducing age-related cognitive decline and neurodegenerative diseases. Recent Findings Recent evidence indicates that nutraceuticals and whole diet approaches may protect against the development of age-related cognitive decline and pathological neurodegeneration. The neuroprotective effects are diverse depending on the nutrient employed and may involve a reduction of neuroinflammation, an activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 77 publications
1
38
1
Order By: Relevance
“…Mainly observational, but also some clinical trials have shown that various single nutrients (B vitamins, vitamin D, polyphenols, n-3 fatty acids), food groups (fish/seafood and vegetables), and dietary patterns (MED: Mediterranean, DASH: Dietary Approaches to Stop Hypertension, MIND: combination of MED and DASH) may protect against the development of age-related cognitive decline and pathological neurodegeneration via various mechanisms 5 7 . These mechanisms include, but not limited to (i) a reduction in neuroinflammation, (ii) an increase in endogenous antioxidant defence, and (iii) a modulation of the gut microbiota structure and function 5 7 . However, the findings to date are not very conclusive and they are heterogenous in terms of cognitive tests administered.…”
Section: Introductionmentioning
confidence: 99%
“…Mainly observational, but also some clinical trials have shown that various single nutrients (B vitamins, vitamin D, polyphenols, n-3 fatty acids), food groups (fish/seafood and vegetables), and dietary patterns (MED: Mediterranean, DASH: Dietary Approaches to Stop Hypertension, MIND: combination of MED and DASH) may protect against the development of age-related cognitive decline and pathological neurodegeneration via various mechanisms 5 7 . These mechanisms include, but not limited to (i) a reduction in neuroinflammation, (ii) an increase in endogenous antioxidant defence, and (iii) a modulation of the gut microbiota structure and function 5 7 . However, the findings to date are not very conclusive and they are heterogenous in terms of cognitive tests administered.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has not been established whether polyphenols can cross the blood–brain barrier (BBB) to directly affect central mechanisms underlying cognitive processes (Schaffer and Halliwell, 2012 ), other physiologically plausible candidate modes of action have been identified. These include (i) reducing neuroinflammation, (ii) modulating the gut microbiota structure and function, (iii) activating the endogenous antioxidant defence system, and (iv) affecting the cardiovascular system to improve neurovascular coupling (Angeloni et al, 2020 ; Lamport and Williams, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, there is a trend to combine together several antioxidants. In fact, synergetic effects of antioxidants have been proved when supplemented in combination [62].…”
Section: Discussionmentioning
confidence: 99%